"Unconventionally Shaped" Antenna Design for UHF RFID Tags. (1st July 2021) - Wang, Silong; Liu, Yulong; Ye, Terry Tao
Abstract : UHF RFID tags need to be attached or embedded into various objects. Unlike traditional free-standing antennas, UHF antenna shapes and form factors may vary significantly. There have been no systematic methods that facilitate the design practice of antenna with unconventional shapes. In this paper, using the geometries of 26 English letters (in capital) as examples, we explore the general methodology of shape-specific antenna design. More specifically, we show that 26 letter geometries can be categorized into 9 groups, and the antennas in each group can be divided and conquered into standard baseline geometries. Through prototypes and measurements, we demonstrate that each letter-shaped antenna, although exhibiting different gains and radiations, can achieve satisfactory performance, as compared to standard UHF dipole antennas. Specifically, letters "M" and "J" achieve the longest reading range of more than 20 meters with a good radiation pattern, which is comparable or even better than many commercial UHF RFID tags.